Analysis of Company Size, Inventory Intensity, and Variability of COGS on The Selection of Inventory Valuation Methods in Basic Materials Sector Companies Listed on IDX 2017-2021 - Fadrul, Fadrul; Howard, Howard; Nurazizah, Febi; Eddy, Pujiono; Novitriansyah, Bob; Estu, Ahmad Zulkarnain (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research purposed to determine the effect of company size, inventory intensity and variability of COGS on the selection of inventory valuation methods in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses secondary data with a sampling technique, namely purposive sampling technique. The number of samples in this study were 31 companies. Descriptive analysis method as well as several types of analysis in this study using SmartPLS software. From this reseach it was concluded that company size has a significant influence on the selection of inventory valuation methods. Meanwhile, inventory intensity and variability of COGS do not have a significant effect on the choice of inventory valuation method.